Neuropsychological functioning of childhood trauma and post-traumatic stress disorder: A meta-analysis. (January 2017) - Malarbi, S.; Abu-Rayya, H.M.; Muscara, F.; Stargatt, R.
Highlights: Children exposed to familial trauma with and without PTSD show impaired cognition. Greatest impairments in cognition are associated with a diagnosis of PTSD. Research on children exposed to non-familial trauma is scarce. Abstract: This study reviewed evidence for cognitive impairments in trauma-exposed children with and without PTSD. Twenty-seven studies were eligible for meta-analysis, totalling 1526 participants, including 412 trauma-exposed children (PTSD unknown), 300 children with PTSD (PTSD+), 323 children without PTSD (PTSD-), and 491 trauma-naive controls. Eligible studies mostly investigated familial-maltreatment trauma ( k  = 22). Trauma-exposed children (PTSD unknown) performed more poorly overall than controls ( d  = −0.57). Cognitive deficits were seen in PTSD+ compared to controls, including a large effect size (ES) for general intelligence ( d  = −0.88), moderate ESs for language/verbal ( d  = −0.65), visuospatial ( d  = −0.53), information processing ( d  = −0.62), learning and memory ( d  = −0.67), and executive skills ( d  = −0.52). PTSD+ showed poorer general intelligence ( d  = −0.28) and visuospatial skills ( d  = −0.42) compared to PTSD-, whilst PTSD- showed poorer executive function ( d  = −0.23) and learning and memory ( d  = −0.61) compared to controls. In conclusion, trauma-exposed children showed cognitive deficits compared to controls, although greatest deficits were associated with PTSD diagnosis.